A new species of the genus Mazaeras Walker, 1855 (Lepidoptera: Erebidae: Arctiinae) - Beccacece, Hernán Mario (2014)
During several days of entomological expedition, as part of a thesis on the phylogeny of Phaegopterina, the first author collected in Northwestern Argentina (provinces of Jujuy and Salta) a series of Mazaeras species previously treated as Mazaeras janeira (Schaus, 1892). The second author, after an expedition in the southern Bolivia (departments of Chuquisaca and Santa Cruz), had a series of specimens of the same taxon also identified as M. janeira (Schaus, 1892). Examination of the male genitalia of the Argentinean specimens showed several differences with the male genitalia of the lectotype of M. janeira. Molecular analysis with specimens of the two taxa confirmed the discrimination. The new species is described and a comparison based both on morphological characters and DNA barcodes with closely related species is provided. The new species can be found in northwestern Argentina (Salta and Jujuy provinces) and southern Bolivia (Santa Cruz, Chuquisaca and Tarija departments) in Yungas montane forest. Mazaeras yungasensis n. sp. can be found between 467m to 2540m (data from Instituto Fundación Miguel Lillo (IFML), Museo de La Plata (MLP), Museo de Zoología de la Universidad Nacional de Córdoba (MZUC) and personal collection: Benoit Vincent (BVC) and Michel Laguerre (MLC) (Fig. 11). Genitalia were prepared using a hot KOH solution (10%). Illustrations images of abdomen and genital male were taken with a camera attached to a stereoscopic microscope Zeiss Stemi 2000-C stereomicroscope. The morphology analyses were made with specimens of IFML, MLP, MZUC, BVC and MLC. Genitalic terminology follows Vincent et al. (2014). One specimen of Mazaeras yungasensis n. sp. and one specimen of M. janeira were sequenced by the second author for provided barcode sequences to confirm the discrimination of these taxa. The sequences were obtained according to the protocol described in Vaglia et al. (2008). Distances between specimens were calculated using Kimura-2-parameters (K2P) model (Kimura, 1980).